Exploring the Relationship Between Internet Use and Mental Health Among Older Adults in England: Longitudinal Observational Study - Lam, Sabrina Sze Man; Jivraj, Stephen; Scholes, Shaun (Journal of medical Internet research, 2020)
There is uncertainty about the impact of internet use on mental health in older adults. Moreover, there is very little known specifically about the impact of particular purposes of internet use. This study aims to investigate the longitudinal relationship between two distinct concepts of mental health with the frequency of internet use among older adults: the moderating role of socioeconomic position (SEP) and the association between specific purposes of internet use. Longitudinal fixed and random effects (27,507 person-years) models were fitted using waves 6-8 of the English Longitudinal Study of Ageing to examine the relationship between different aspects of internet use (frequency and purpose) and two mental health outcomes (depression and life satisfaction). The potential moderating effect of SEP on these associations was tested using interaction terms. Infrequent internet use (monthly or less vs daily) was predictive of deteriorating life satisfaction (β=-0.512; P=.02) but not depression. Education and occupational class had a moderating effect on the association between frequency of internet use and mental health. The associations were stronger in the highest educational group in both depression (P=.09) and life satisfaction (P=.02), and in the highest occupational group in life satisfaction (P=.05) only. Using the internet for communication was associated with lower depression (β=-0.24; P=.002) and better life satisfaction (β=.97; P<.001), whereas those using the internet for information access had worse life satisfaction (β=-0.86; P<.001) compared with those who did not. Policies to improve mental health in older adults should encourage internet use, especially as a tool to aid communication.